2002
DOI: 10.1002/pola.10302
|View full text |Cite
|
Sign up to set email alerts
|

Controlled radical polymerization of 2‐hydroxyethyl methacrylate with a hydrophilic ruthenium complex and the synthesis of amphiphilic random and block copolymers with methyl methacrylate

Abstract: A hydrophilic ruthenium complex with ionic phosphine ligands {1: RuCl2[P(3‐C6H4SO3Na)(C6H5)2]2} induced controlled radical polymerization of 2‐hydroxyethyl methacrylate (HEMA) in methanol under homogeneous conditions; the initiator was a chloride (R‐Cl) such as CHCl2COPh. The number‐average molecular weights of poly(HEMA) increased in direct proportion to monomer conversion, and the molecular weight distributions were relatively narrow (Mw/Mn = 1.4–1.7). A similar living radical polymerization was possible wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…As expected for any living polymerization, each of the product polymers carries an initiator fragment (the isobutyrate in the example) at the α end, and we have indeed shown that end‐functionalized polymers can be synthesized with our RuCl 2 (PPh 3 ) 3 ‐based systems coupled with functionalized initiators [Scheme (B)] 21. The key to the synthesis is that the ruthenium(II) catalyst is robust toward polar functional groups, such as amines, alcohols, and amides, in the initiator and at the α end of the products 21, 22…”
Section: Introductionmentioning
confidence: 91%
“…As expected for any living polymerization, each of the product polymers carries an initiator fragment (the isobutyrate in the example) at the α end, and we have indeed shown that end‐functionalized polymers can be synthesized with our RuCl 2 (PPh 3 ) 3 ‐based systems coupled with functionalized initiators [Scheme (B)] 21. The key to the synthesis is that the ruthenium(II) catalyst is robust toward polar functional groups, such as amines, alcohols, and amides, in the initiator and at the α end of the products 21, 22…”
Section: Introductionmentioning
confidence: 91%
“…Another modification was directed to give a hydrophilic nature to ruthenium complexes ( 7 and 8 ),26,27 which is better suited for hydrophilic monomers, polymerization in aqueous media, and catalyst removal. This topic will be described later in this review.…”
Section: Evolution Of Catalysts: Versatility and Activitymentioning
confidence: 99%
“…We thus developed a variety of metal catalysts for living‐radical polymerization of various monomers, which now include methacrylates,9,12,13,16,20 acrylates,16,31 styrenes,12,16,29 acrylamides,32,41 vinyl acetate,33 olefins,34 and monomers with polar functional groups26,42 (Figure 5).…”
Section: Evolution Of Catalysts: Versatility and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…25 This rendered previous controlled radical polymerizations of HEMA, reliable only in alcohols or mixed solvents with water. 26,27 In contrast, the catalytic system with PPh 2 (pPhOH) allowed a controlled aqueous polymerization of HEMA (Figure 7). The polymerization proceeded smoothly, without insoluble or crosslinked products, and the polymers showed narrow MWDs (reaching M w /M n ¼1.28 at a higher conversion).…”
Section: Reduction Of Catalyst Dosementioning
confidence: 99%